Guide :

# what fration is equal to 5% out of 100%

i need this probem now plz.

## Research, Knowledge and Information :

### Equivalent Fractions - Math Is Fun

Equivalent Fractions. Equivalent Fractions have the same value, even though they may look different. These fractions are really the same: 1 2 = 2 4 = 4 8
Read More At : www.mathsisfun.com...

### Equivalent Fractions Calculator

What are equivalent fractions and how to find them. Multiply the numerator and denominator by the same whole number to create an equivalent fraction. Calculator finds ...
Read More At : www.calculatorsoup.com...

### Fractions Overview - Math is Fun - Maths Resources

The bottom number says how many equal slices it was cut into ... Equivalent Fractions. Some fractions may look ... Visit the Fractions Index to find out even more.
Read More At : www.mathsisfun.com...

### Fraction (mathematics) - Wikipedia

It is easy to work out the chosen type of fraction to convert to; ... and change each fraction to an equivalent fraction with the chosen common denominator.
Read More At : en.wikipedia.org...

### What fraction out of 1000 equals 4 out of 5? - Weknowtheanswer

What fraction out of 1000 equals 4 out of 5? Find answers now! No. 1 Questions & Answers Place.
Read More At : www.weknowtheanswer.com...

### Fraction to percent conversion calculator - RapidTables.com

Percent to fraction converter How to convert fraction to percent. For example, in order to get a decimal fraction, 3/4 is expanded to 75/100 by multiplying the ...
Read More At : www.rapidtables.com...

### Equivalent fractions (video) | Fractions | Khan Academy

Learn how to write equivalent fractions. ... we'll get an equivalent fraction. ... And all we did is we figured out a different way of writing 21/35.
Read More At : www.khanacademy.org...

### IXL - Fractions with denominators of 10, 100, and 1000 (4th ...

Improve your skills with free problems in 'Fractions with denominators of 10, 100, and 1000' and thousands of other practice lessons. ... SmartScore out of 100. 0.
Read More At : www.ixl.com...

### How do you write 1.5 as a fraction? | Reference.com

If there were two, as in .35, the fraction would be multiplied by 100. Now, the answer appears as 5/10. When this number is further reduced, ...
Read More At : www.reference.com...

## Suggested Questions And Answer :

### Urgent! Please help!

y=sqrt(x)-4x, 0<=x <=4 max: at x=0, y=0 . . min: at x=4, y=2-8=-6
Read More: ...

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}
Read More: ...

### show that the function f(x)= sqrt (x^2 +1) satisfies the 2 hypotheses of the Mean Value Theorem

f(x) = sqrt(x^2 + 1) ; [(0, sqrt(8)] Okay, so for the Mean Value Theorem, two things have to be true: f(x) has to be continuous on the interval [0, sqrt(8)] and f(x) has to be differentiable on the interval (0, sqrt(8)). First find where sqrt(x^2 + 1) is continous on. We know that for square roots, the number has to be greater than or equal to zero (definitely no negative numbers). So set the inside greater than or equal to zero and solve for x. You'll get an imaginary number because when you move 1 to the other side, it'll be negative. So, this means that the number inside the square root will always be positive, which makes sense because the x is squared and you're adding 1 to it, not subtracting. There would be no way to get a negative number under the square root in this situation. Therefore, since f(x) is continuos everywhere, (-infinity, infinity), then f(x) is continuous on [0, sqrt(8)]. Now you have to check if it is differentiable on that interval. To check this, you basically do the same but with the derivative of the function. f'(x) = (1/2)(x^2+1)^(-1/2)x2x which equals to f'(x) = x/sqrt(x^2+1). So for the derivative of f, you have a square root on the bottom, but notice that the denominator is exactly the same as the original function. Since we can't have the denominator equal to zero, we set the denominator equal to zero and solve to find the value of x that will make it equal to zero. However, just like in the first one, it will never reach zero because of the x^2 and +1. Now you know that f'(x) is continous everywhere so f(x) is differentiable everywhere. Therefore, since f(x) is differentiable everywhere (-infinity, infinity), then it is differentiable on (0, sqrt(8)). So the function satisfies the two hypotheses of the Mean Value Theorem. You definitely wouldn't have to write this long for a test or homework; its probably one or two lines of explanation at most. But I hope this is understandable enough to apply to other similar questions!
Read More: ...

### Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}
Read More: ...

### find the intercepts with the axes or asymptotes : y=2sin(3x+30deg) with domain -pie/3 <or equals to x < or equals to pie/2

y-intersept be weer x=0, so plug in intu y=2*sine(3x+30 deg) y=2*sine(30) at x=0 sine(30 deg)=0.5, so y=2*0.5=1 x-intersept...set y=0, so 2*sine(3x+30)=0 so sine(3x+30)=0 sine=0 at (....)=0, so 3x+30=0 so 3x=-30 x=-10 deg
Read More: ...

### integral from 0 to pi where f(x)= 5sinx if 0<or equal to x<pi/2, 3cosx if pi/2<or equal to x<pi

answer this problem:Find the DEFINISI INTEGRAL FOURIER  representation of the function ,f(x)={0 ,x<0 } f(x)=pi/2 x=0,f(x)=pi*exp^x x>0
Read More: ...

### 3x squared minus 7x equals 0

3x squared minus 7x equals 0 in my math homework...solve the quadratic equations by factoring 3x^2 - 7x = 0 When we factor this, we will have: (3x + a)(x + b) = 0 We need an a and b such that 3b + a = -7, and ab = 0. We know ab has to equal zero, because there is no constant term following the 7x. If we set a = 0 and b = -7/3, we will have what we are looking for. (3x + 0)(x - 7/3) = 0 Multiply that out, and we get: 3x^2 + 0x - 3(7/3)x - 0 = 0 3x^2 + 0x - 7x - 0 = 0 3x^2 - 7x = 0,  which is what we started with.
Read More: ...

### Find the solution set for each rational inequation. Graph the solution set on a number line.

(x+3)(x-2)/((x+2)(x-1))≥0. We need to look at various intervals marked by -3, -2, 1, 2 on the number line. x≤-3 satisfies the inequality; -3-3. (x-2)/(x^2-3x-10)<0. This is (x-2)/((x-5)(x+2))<0. Disallowed values are 5 and -2. Significant values are -2, 2, 5; x<-2 satisfies; -25 fails.
Read More: ...

### n^3-9n^2+20n prove that it is divisible by 6 for all integers n greater or equal to 1

Factor the given expression.   We have: n³-9n²+20n=n(n-4)(n-5) ··· Ex.1 If Ex.1 is divisible by 6, Ex.1 is also divisible by two prime factors of 6, 2 and 3. (6=2x3) A. If n is odd, (n-5) is even.   If n is even, (n-4) is also even.   Therefore, n(n-4)(n-5) is always a multiple of 2. B. If Exp.1 is divisible by 3, the remainder is 0,1,or 2. If n ≡ 0 (mod 3), n-4 ≡ -4 ≡ -1 (mod 3), and n-5 ≡ -5 ≡ -2 (mod 3), that is: n is a multiple of 3. If n ≡ 1 (mod 3), n-4 ≡ -3 ≡ 0 (mod 3), and n-5 ≡ -4 ≡ -1 (mod 3), that is: (n-4) is a multiple of 3. If n ≡ 2 (mod 3), n-4 ≡ -2 (mod 3), and n-5 ≡ -3 ≡ 0 (mod 3), that is: (n-5) is a multiple of 3. Therefore, n(n-4)(n-5) is always a multiple of 3. CK: If n=1, n(n-4)(n-5)=1(-3)(-4)=12, 12(n=2), 6(n=3), 0(n=4), 0(n=5), 12, 42, 96, 180 … CKD.  Therefore, n³-9n²+20n is divisible by 6 for all integers greater than or equal to 1.
Read More: ...

### (13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: x + -3x = -2x -3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Reorder the terms: -3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2 Combine like terms: 5 + -5 = 0 -3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2 -3 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 -3 + -2x + x2 = 0 + -1x2 + x2 -3 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 -3 + -2x + x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-1, 3}
Read More: ...

#### Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
• Start your question with What, Why, How, When, etc. and end with a "?"
• Be clear and specific
• Use proper spelling and grammar
all rights reserved to the respective owners || www.math-problems-solved.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1489 seconds